The Clinical Frailty Scale: Estimating the Prevalence of Frailty in Older Patients Hospitalised with COVID-19. The COPE Study - Jemima T. Collins; Roxanna Short; Ben Carter; Alessia Verduri; Phyo K. Myint; Terence J. Quinn; Arturo Vilches-Moraga; Michael J. Stechman; Susan Moug; Kathryn McCarthy; Jonathan Hewitt (Geriatrics, 2020)
Frailty assessed using Clinical Frailty Scale (CFS) is a good predictor of adverse clinical events including mortality in older people. CFS is also an essential criterion for determining ceilings of care in people with COVID-19. Our aims were to assess the prevalence of frailty in older patients hospitalised with COVID-19, their sex and age distribution, and the completion rate of the CFS tool in evaluating frailty. Methods: Data were collected from thirteen sites. CFS was assessed routinely at the time of admission to hospital and ranged from 1 (very fit) to 9 (terminally ill). The completion rate of the CFS was assessed. The presence of major comorbidities such as diabetes and cardiovascular disease was noted. Results: A total of 1277 older patients with COVID-19, aged ≥ 65 (79.9 ± 8.1) years were included in the study, with 98.5% having fully completed CFS. The total prevalence of frailty (CFS ≥ 5) was 66.9%, being higher in women than men (75.2% vs. 59.4%, p < 0.001). Frailty was found in 161 (44%) patients aged 65–74 years, 352 (69%) in 75–84 years, and 341 (85%) in ≥85 years groups, and increased across the age groups (<0.0001, test for trend). Conclusion: Frailty was prevalent in our cohort of older people admitted to hospital with COVID-19. This indicates that older people who are also frail, who go on to contract COVID-19 may have disease severity significant enough to warrant hospitalization. These data may help inform health care planners and targeted interventions and appropriate management for the frail older person.